Innovative mechanisms of action for pharmaceutical cognitive enhancement: A systematic review. Issue 1 (30th September 2015) - Fond, Guillaume; Micoulaud-Franchi, Jean-Arthur; Brunel, Lore; Macgregor, Alexandra; Miot, Stéphanie; Lopez, Régis; Richieri, Raphaëlle; Abbar, Mocrane; Lancon, Christophe; Repantis, Dimitris
Abstract: Pharmacological cognitive enhancement refers to improvement in cognitive functions after drug use in healthy individuals. This popular topic attracts attention both from the general public and the scientific community. The objective was to explore innovative mechanisms of psychostimulant's action, whose potential effectiveness was assessed in randomized placebo-controlled trials (RCTs). A systematic review was carried out, using the words "attention", "memory", "learning", "executive functions", and "vigilance/wakefulness" combined to "cognitive enhancer" or "smart drug". Methylphenidate, amphetamines, modafinil, nicotine, acetylcholine esterase inhibitors and antidepressants were extensively studied in previous meta-analyses and were not included in the present work. Drugs were classified according to their primary mode of action, namely catecholaminergic drugs (tolcapone, pramipexole, guanfacine), cholinergic drugs (anticholinergics), glutamatergic drugs (ampakines), histaminergic drugs, and non-specified (glucocorticoids). Overall, 50 RCTs were included in the present review. In conclusion, a number of new active drugs were found to improve some cognitive functions, in particular verbal episodic memory. However the number of RCTs was limited, and most of the studies found negative results. Future studies should assess both effectiveness and tolerance of repeated doses administration, and individual variability in dose response (including baseline characteristics and potential genetic polymorphisms). One explanation for the limited number of recent RCTs with new psychostimulants seems to be the ethical debate surrounding pharmaceutical cognitive enhancement in healthy subjects. Highlights: Methylphenidate, modafinil and nicotine were found to enhance some cognitive functions. Tolcapone and levo-dopa, exhibited enhancement properties in verbal episodic memory and encoding. Negative results were found for pramipexole, guanfacine, clonidine ampakines and fexofenadine. Conflicting results were found with hydrocortisone and anticholinergic drugs. There was no RCT assessing piracetam, piracetam-like molecules and phosphodiesterase inhibitors.